KATAKANA-ENGLISH HYBRIDS IN YOUTH CULTURE AND THEIR IMPLICATIONS FOR LANGUAGE TEACHING (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The essence of this thesis lies in exploring the increasing integration of English-based katakana words in Japanese youth culture and their implications for language pedagogy. Expressions such as "menbure"